The nondestructive evaluation of the GFRP composite plate with an elliptical hole under fatigue loading conditions. (November 2018) - Stawiarski, Adam
Highlights: The wave propagation method and the infrared thermography have been considered. The fatigue damage evolution in the composite plate with hole has been observed. The active measurement technique was proposed with the use of PZT transducers. Thermographic monitoring of the specimens subjected to fatigue load was introduced. The comparison of the intact and defected structures was used by damage detection algorithm. Abstract: The accurate assessment of the fatigue strength for structures made of composite materials is difficult because of the great number of possible failure forms. The Structural Health Monitoring (SHM) systems are developed and applied in engineering structures for permanent monitoring the state of the constructions. In this paper the Lamb wave propagation method and the infrared thermography were applied to observe the fatigue damage evolution in the multilayered composite plate with an elliptical hole in the middle. The active pitch-catch measurement technique was introduced based on the surface mounted piezoelectric transducers. The localization of the piezoelectric actuator and sensors responsible for excitation and detection of the elastic wave was chosen based on the progressive failure analysis applied in finite element method. The multipoint measuring system was responsible for analysis of the elastic wave propagation phenomenon during the fatigue tests. The sequential measurement of the elastic wave parameters allow one to observe the state of the structure. The different parameters describing the wave propagation phenomenon like amplitude and time of flight was considered. The infrared thermography make possible of detection of the damage initiation and permanent monitoring of the structure. The measurement of the temperature distribution is straightforward and doesn't need complicated algorithms and software. Application of the coupled approach to the damage detection (piezoelectric transducers in SHM system with the permanent surface temperature monitoring) allow one to build cost effective system for detection of the damage initiation and for monitoring failure form evolution.